2012
DOI: 10.7589/0090-3558-48.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Black-Backed Jackal Exposure to Rabies Virus, Canine Distemper Virus, and Bacillus Anthracis in Etosha National Park, Namibia

Abstract: Canine distemper virus (CDV) and rabies virus (RABV) occur worldwide in wild carnivore and domestic dog populations and pose threats to wildlife conservation and public health. In Etosha National Park (ENP), Namibia, anthrax is endemic and generates carcasses frequently fed on by an unusually dense population of black-backed jackals (Canis mesomelas). Using serology and phylogenetic analyses (on samples obtained from February, 2009 to July, 2010), and historical mortality records (1975–2011), we assessed jacka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 44 publications
(47 reference statements)
0
60
0
2
Order By: Relevance
“…Initial laboratory data from the 1960s indicated that dogs were resistant to systemic anthrax infection (Gleiser et al 1968); however, these conclusions were based on experimental respiratory inoculation of dogs with anthrax spores. Field data from the past 30 years indicate that domestic and wild canids can be susceptible to anthrax infection through ingestion of infected carcasses (McGee et al 1994, Creel et al 1995, although at the same time serological results suggest canids may be exposed often and have a relatively high resistance (Bellan et al 2012). Lembo et al (2011) suggested that domestic dogs be used as sentinel species to detect anthrax epizootics based on findings that domestic dog anthrax seroprevalence shadowed the levels detected in livestock and wild ungulates in Tanzania.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Initial laboratory data from the 1960s indicated that dogs were resistant to systemic anthrax infection (Gleiser et al 1968); however, these conclusions were based on experimental respiratory inoculation of dogs with anthrax spores. Field data from the past 30 years indicate that domestic and wild canids can be susceptible to anthrax infection through ingestion of infected carcasses (McGee et al 1994, Creel et al 1995, although at the same time serological results suggest canids may be exposed often and have a relatively high resistance (Bellan et al 2012). Lembo et al (2011) suggested that domestic dogs be used as sentinel species to detect anthrax epizootics based on findings that domestic dog anthrax seroprevalence shadowed the levels detected in livestock and wild ungulates in Tanzania.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, anthrax has been suspected in wild North American wolves (Canis lupus) during bison outbreaks (Shury et al 2009) and confirmed in African wild dogs (Lycaon pictus) (Creel et al 1995). Likewise, black-backed jackals (Canis mesomelas) in Namibia (Bellan et al 2012) and coyotes (Canis latrans) in North America (Mongoh et al 2008) have both been associated with scavenging during anthrax outbreaks. Each of these examples illustrates the importance of considering canids, whether wild or domestic, as potentially susceptible scavengers.…”
Section: Discussionmentioning
confidence: 95%
“…This study was conducted on the Okaukuejo plains of ENP, where anthrax is seasonally endemic and causes significant mortality in zebras (Equus quagga), springboks (Antidorcas marsupialis), elephants (Loxodonta africanus), wildebeests (Connochaetes taurinus), and occasionally other herbivores (20). The carrion produced by anthrax deaths feeds a diverse assemblage of vertebrate scavengers, including most frequently black-backed jackals (Canis mesomelas), spotted hyenas (Crocuta crocuta), white-backed vultures (Gyps africanus), lappet-faced vultures (Torgos tracheliotos), marabou storks (Leptoptilos crumeniferus), and occasionally lions (Panthera leo), black crows (Corvus capensis), pied crows (Corvus albus), and various other raptor species (20,31,32).…”
Section: Methodsmentioning
confidence: 99%
“…Rö ttcher and Sawchuk (1978) found jackals were the dominant wildlife reservoir for rabies in Zambia. Bellan et al (2012) documented apparent asymptomatic rabies infections in jackals in Namibia and suggested the strain was closely related to that found in domestic dogs and other terrestrial wildlife. Thus, we believe lions would have less probability of contact with a lyssavirus-infected sick bat than with a rabies virus-infected terrestrial carnivore.…”
Section: Berentsen Et Almentioning
confidence: 84%